Correlation between the water drinking test and modified diurnal tension curve in untreated glaucomatous eyes (Clinics, 2008)
OBJECTIVES: To investigate the correlation and agreement between the intraocular pressure peaks detected during the water drinking test and the modified diurnal tension curve in untreated glaucomatous eyes. INTRODUCTION: It has been suggested that the intraocular pressure peaks detected during the water drinking test predict the peaks observed during a 24-hour diurnal tension curve. A more feasible and practical test for assessing intraocular pressure peaks in glaucomatous eyes during office hours would be of great clinical utility. METHODS: This was a prospective study involving open angle glaucoma patients without anti-glaucoma medication submitted to the modified diurnal tension curve and water drinking test on the same day. The intraocular pressure peaks during the water drinking test and the modified diurnal tension curve were reported and compared. Statistical analysis was performed to assess the correlation and agreement between intraocular pressure peak measurements. RESULTS: The correlation between intraocular pressure peaks during the water drinking test and modified diurnal tension curve was significant and strong (Pearson's Correlation Coefficient r=0.780, p